Characterization of diverse 2,4-dichlorophenoxyacetic acid-degradative plasmids isolated from soil by complementation. - Top, E M (1995)
The diversity of 2,4-dichlorophenoxyacetic acid (2,4-D)-degradative plasmids in the microbial community of an agricultural soil was examined by complementation. This technique involved mixing a suitable Alcaligenes eutrophus (Rifr) recipient strain with the indigenous microbial populations extracted from soil. After incubation of this mixture, Rifr recipient strains which grow with 2,4-D as the only C source were selected. Two A. eutrophus strains were used as recipients: JMP228 (2,4-D-), which was previously derived from A. eutrophus JMP134 by curing of the 2,4-D-degradative plasmid pJP4, and JMP228 carrying pBH501aE (a plasmid derived from pJP4 by deletion of a large part of the tfdA gene which encodes the first step in the mineralization of 2,4-D). By using agricultural soil that had been treated with 2,4-D for several years, transconjugants were obtained with both recipients. However, when untreated control soil was used, no transconjugants were isolated. The various transconjugants had plasmids with seven different EcoRI restriction patterns. The corresponding plasmids are designated pEMT1 to pEMT7. Unlike pJP4, pEMT1 appeared not to be an IncP1 plasmid, but all the others (pEMT2 to pEMT7) belong to the IncP1 group. Hybridization with individual probes for the tfdA to tfdF genes of pJP4 demonstrated that all plasmids showed high degrees of homology to the tfdA gene. Only pEMT1 showed a high degree of homology to tfdB, tfdC, tfdD, tfdE, and tfdF, while the others showed only moderate degrees of homology to tfdB and low degrees of homology to tfdC.(ABSTRACT TRUNCATED AT 250 WORDS)